BRAND HEXAGON MODEL: MENGANGKAT IDENTITAS LOKAL SEBAGAI BRAND VALUE DESA WISATA - Asriandhini, Bunga; lestari, Umi (Penerbit CV Tentrem Karya Nusa, 2021)
Melung Tourism Village has natural, agricultural, social, and cultural potential which can be developed in support of the concept of sustainable tourism. One of the efforts is to explore the local potential that becomes the Melung Tourism Village, a uniqueness that is valueable in the minds of community. The Brand Hexagon Model is model formulated by Simon Anholt which aims to find brand values based on perceptions of the public/tourist. The research method uses descriptive qualititative research. This research found the brand values of Melung Tourism Village, robusta coffee, the beauty of its scenery, and the friendliness of local people who are still closely carriying out the tradition Key Words: Brand Value; Melung Tourism Village; Local Identity